Not Applicable Comparative Hospitality Eco-profiles of two Nature-rich Locations of the Indian Sundarbans: Not Applicable - Bardhan, Suchandra (Turizam, 2025)
The hospitality sector comprising different types of tourist accommodations is an integral part of the tourism industry. In light of climate change concerns, sustainable development, and responsible behaviour, these accommodation establishments like hotels, lodges, and guest houses need to commit to the wise use of environmental resources like land, air, water, and energy. Efficient management of Carbon emissions, consumption of fresh water, and fossil fuel-based energy are imperative to ensure their resilience and acceptable environmental performance. This requires meticulous study and assessment of these parameters leading to the hospitality eco-profiling of a particular destination. This paper aims to present the baseline eco-profiles of the tourist establishments of both Jharkhali and Bakkhali - the two nature-based destinations of the Indian Sundarbans. The result is visualized in the form of a comparative eco-profile diagram for these two locations. The methodology involves the selection of parameters, field data collection through primary survey in the two locations, multi-stage documentation in predefined formats, and finally, computation of the values of the parameters. The seven parameters selected for comparison and their respective units are total bed capacity in numbers, average built-up area/lodge in m2, user water intensity in litres per head (guest) per day (lphd), water consumption index in kl/m2/year, energy performance index in kWh/m2/year, the capacity of captive electricity generator in kVA, and Carbon emission in kgC/m2/year. It was found that Bakkhali being a more mature destination with greater tourist visitations has much higher values for most parameters than Jharkhali. This first-ever eco-profiling exercise for the hospitality establishments in these two eco-sensitive tourist destinations is expected to help in monitoring the environmental performance of each hospitality unit, and also act as a reference for developing a regulatory framework and environmental management plan for the ecologically fragile Indian Sundarbans by the tourism administrators, planners and managers.
Keywords: Environmental footprint of hospitality buildings, Carbon emission, energy performance, water consumption index, user water intensity, sustainable development goals